Management of the Tilawatil Qur'an Development Institute in Realizing Quality Qori-Qoriah in Langkat Regency - Heri Suseno; Farhan Indra (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This journal investigates the extent to which the management of the Tilawatil Quran Development Institute (LPTQ) plays an important role in achieving high quality standards for qori and qoriah in Langkat Regency. This study analyzes the various management strategies implemented by LPTQ to improve recitation competence among participants, especially qori and qoriah. Using qualitative research methods, data were collected through interviews, observations, and analysis of relevant documents. The results highlighted the success of LPTQ in designing and implementing structured training programs, managing recitation competitions, and fully supporting the development of individual potential. LPTQ's active role in building networks with recitation experts and related parties is also an important factor in encouraging the quality of qori and qoriah in this region. However, the research also identified some challenges, including limited resources and lack of community participation. As such, this journal provides an in-depth understanding of how LPTQ management can be key in producing quality qori and qoriah, while highlighting the opportunities and constraints faced by the institution. The implication of these findings is that strengthening LPTQ management can form a solid foundation for creating a supportive environment for the optimal growth and development of qori and qoriah in Langkat Regency.